Effect of extracorporeal shock wave therapy on nerve conduction: a systematic review and meta-analysis - Yang, Liuxin; Li, Xuan; Li, Shuhan; Yang, Jiao; Meng, Dianhuai (Frontiers in Neurology, 2024)
BackgroundExtracorporeal shock wave therapy (ESWT), as a non-invasive physical agent modality, was effective in relieving spasticity, reducing pain, and improving dysfunction. This systematic review and meta-analysis aimed to investigate the effect of ESWT on nerve conduction, and to find out whether the ESWT group is superior to the control or other comparison groups, thus providing support for guiding the rehabilitation of peripheral nerve injury in clinical work.MethodsPubMed, Web of Science, the Cochrane Library, and Embase were searched from inception to August 20, 2024. This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and registered in the PROSPERO database (registration number CRD42024500891). It aimed to compare (1) the ESWT group (ESWT) and baseline, and (2) subgroup analyses: ESWT and the control group (Control), ESWT and the local corticosteroid injection group (LCI), ESWT combined with physical therapy (ESWT + PT) and PT alone, and ESWT and PT. Outcome indicators extracted were nerve conduction study results: sensory nerve action potential (SNAP) amplitude, SNAP distal latency, sensory nerve conduction velocity (SNCV), compound muscle action potential (CMAP) amplitude, motor nerve distal latency (MNDL), motor nerve conduction velocity (MNCV), H/M ratio and H-reflex latency.ResultsA total of 879 papers were identified through the database searches. Twenty-four trials were included in the systematic review, and 22 trials were included in the meta-analysis. The results showed that: (1) compared to the baseline, ESWT reduced SNAP distal latency mid-term (MD, −0.39; 95% CI: −0.52, −0.26; I2 = 85%), and improved SNCV both short-term (MD, 4.36; 95% CI: 1.23, 7.49; I2 = 91%) and mid-term (MD, 2.65; 95% CI: 1.79, 3.51; I2 = 61%). At the same time, it reduced MNDL short-term (MD, −0.61; 95% CI: −0.91, −0.30; I2 = 92%), but had no significant effect on MNCV. (2) Subgroup analyses showed that ESWT was superior to Control but not significantly better than LCI, especially in SNCV. The excitatory effect of ESWT + PT on the sensory and motor nerves was significantly better than that of PT alone.ConclusionESWT had some excitatory effect on peripheral nerves, especially on sensory nerve studies. Although the efficacy of this treatment was superior to that of the control group, and the combined treatment with PT was more effective than PT alone, its efficacy might not exceed that of LCI.Systematic review registrationUnique identifier: PROSPERO (CRD42024500891).